Sarcopenia, healthy living, and mortality in patients with chronic liver diseases - Van Dongen, Catherine; Paik, James M.; Harring, Michael; Younossi, Youssef; Price, Jillian K.; Kabbara, Khaled; Golabi, Pegah; Younossi, Zobair M. (Hepatology communications, 2022)
Chronic liver diseases (CLDs) are associated with increased morbidity and mortality. Sarcopenia is an important complication of CLD that can be impacted by several modifiable risk factors. Our aim was to assess the associations between healthy living, sarcopenia, and long‐term outcomes among patients with CLD. We used the Third National Health and Nutrition Examination Survey data with National Death Index–linked mortality files. We used the American Heart Association's Life's Simple 7 (LS7) metrics as surrogates of healthy living. The study included 12,032 subjects (34.9% CLDs [0.5% hepatitis B virus (HBV), 1.8% hepatitis C virus (HCV), 5.7% alcohol‐associated liver disease (ALD), 26.9% nonalcoholic fatty liver disease (NAFLD)] and 65.1% controls). Prevalence of sarcopenia was higher among NAFLD than other CLDs and the controls (40.7% in NAFLD, 27.2% in ALD, 22.4% in HCV, 16.8% in HBV, and 18.5% in controls; p < 0.001). Among NAFLD and ALD, patients with sarcopenia were less likely to meet ideal LS7 metrics than those without sarcopenia. During 27 years of follow‐up, among 4 patients with CLDs and the controls, all‐cause cumulative mortality was highest among patients with HCV (35.2%), followed by ALD (34.7%) and NAFLD (29.6%). The presence of sarcopenia was associated with higher risk of all‐cause mortality only among subjects with NAFLD (hazard ratio [HR] 1.24; 95% confidence interval [CI] 1.01–1.54; p = 0.04). Among subjects with NAFLD, presence of sarcopenia was associated with higher risk of cardiovascular‐specific (HR 2.28 [1.71–3.05; p < 0.01]), cancer‐specific (HR 1.90 [1.37–2.65]; p < 0.01), diabetes‐specific (HR 6.42 [2.87–14.36]; p < 0.01), and liver‐specific mortality (HR 2.49 [1.08–5.76]; p = 0.04). The multivariable model showed that component of LS7 metrics that provided the strongest protection against sarcopenia were ideal body mass index, ideal blood pressure, ideal physical activity, and ideal glycemic control among subjects with NAFLD subjects. Conclusions: Among subjects with NAFLD, sarcopenia is associated with a higher risk of all‐cause mortality and liver mortality. Attainment of ideal LS7 metrics provides protection against sarcopenia in NAFLD. Chronic liver diseases (CLDs) are associated with increased morbidity and mortality. Sarcopenia is an important complication of CLD. Among CLDs, NAFLD and ALD patients have worse LS7 patterns. Among NAFLD subjects, sarcopenia is associated with a higher risk of all‐cause mortality (especially among lean NAFLD) and liver mortality (especially among females). Attainment of ideal LS7 metrics provides protection against sarcopenia in NAFLD.